2009
DOI: 10.1002/mawe.200800410
|View full text |Cite
|
Sign up to set email alerts
|

Improved osseointegration of a novel, hydrophilic Ti surface – a review

Abstract: The high surface energy of sandblasted and acid etched (SLA) titanium surfaces can be retained by keeping them submersed in an isotonic NaCl solution at pH 4 to 6 under a nitrogen atmosphere immediately after the acid-etching process, thus reducing the adsorption of potential contaminants from the atmosphere. The novel implant surface thus produced shows a strongly increased hydrophilicity, compared to the conventional SLA surface, and is named SLActive.Several animal studies have indicated a faster osseointeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Apatite nucleation is initiated by adsorption of Ca 2+ ions, followed at a later stage by incorporation of phosphate groups and formation of an amorphous calcium phosphate phase. Several studies have shown that the bone apposition process is favored by the presence of hydroxyl groups on the oxide film. This hydroxylation occurs naturally when the TiO 2 surface is exposed to water contained in air, thus forming acidic and basic OH groups.…”
Section: Introductionmentioning
confidence: 99%
“…Apatite nucleation is initiated by adsorption of Ca 2+ ions, followed at a later stage by incorporation of phosphate groups and formation of an amorphous calcium phosphate phase. Several studies have shown that the bone apposition process is favored by the presence of hydroxyl groups on the oxide film. This hydroxylation occurs naturally when the TiO 2 surface is exposed to water contained in air, thus forming acidic and basic OH groups.…”
Section: Introductionmentioning
confidence: 99%
“…26,29-32 Microtextured Ti surfaces that are hydrophilic enhance tissue integration of titanium implants, especially during the early healing stages in vivo. 26,29,30,3336 Surface chemistry also plays an important role in regulating the signaling pathways and downstream cell differentiation. 37,38 In order to reduce healing time and enhance osseointegration in compromised patients, it is important to understand, optimize, and engineer ideal surface properties for dental and orthopaedic implants used in bone applications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Ti surface properties, such as surface roughness, surface energy, and surface chemistry, influence bone formation. Surface roughness on the micrometer scale can enhance osteoblast differentiation in vitro. , Microtextured Ti surfaces that are hydrophilic enhance tissue integration of titanium implants, especially during the early healing stages in vivo. ,,, Surface chemistry also plays an important role in regulating the signaling pathways and downstream cell differentiation. , In order to reduce healing time and enhance osseointegration in compromised patients, it is important to understand, optimize, and engineer ideal surface properties for dental and orthopaedic implants used in bone applications.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, SLA is a composite technique which includes sandblasting and acid-etching. The method not only makes the superposition of macro/micro topography of the implant surface, but also facilitates the surface mechanical properties and corrosion protection [5,6].…”
Section: Introductionmentioning
confidence: 99%